Design of experiment study on Puyat Steel Corporation - Baquiran, Francis Allan (College of Engineering, 2001)
Puyat Steel Corporation is a large scale manufacturing company engaged in the manufacture of galvanized and prepainted galvanized sheets and coils, roofing and walling profiles, bended accessories and steel purlins. All of these products undergo one main continuous production process. The base metal, in the form of coils, is coated with zinc to produce galvanized iron that is highly resistant to corrosion. Zinc is three times more expensive than steel and so the coating must be minimized. However, the government has set-up zinc coating thicknesses that are being strictly enforced. This becomes the biggest concern of the company in its production department. Through interview and observation, two factors were identified as having a major effect in the coating thicknesses. These were : distance of the air knives from the specimen, and the air pressure of the air wiping system. Both factors are controllable and so an experiment was designed werein the two factors were controlled at three predefined levels each. The resulting zinc coating thickness was analyzed using analysis of variance or ANOVA and the significant factors were identified, namely : the air pressure of the air wiping system, and the interaction between the two factors mentioned earlier. A linear regression model was then developed from the resulting significant factors. Recommendations were then made for the company as to what production factors should be carefully taken care of.